Film Disney Sebagai Medium Woke Culture: Politik Multikulturalisme Dalam Film Stange World (2022) Dan Lightyear (2022) - Azizah Nur Aulia; Dwi Ayu Setiowati; Chairunisa Chairunisa (Riviera Publishing, 2025)
This study examines the construction of woke culture, gender, and multicultural politics in Disney’s Strange World (2022) and Lightyear (2022) using Christian Metz’s semiotic approach. The research focuses on how visual elements and cinematic structures—central to Visual Communication Design—are employed to construct LGBTQ identities and messages of inclusivity. Through the analysis of Metz’s syntagmatic categories such as scene, descriptive syntagma, and autonomous shot, the study reveals that Disney strategically constructs ideological meaning through imagery, visual narratives, and cinematic symbols. These films function not merely as narratives but as instruments of social construction that reshape public perceptions of gender and diversity. This construction process is manifested through deliberate visual techniques, character dynamics, and scene compositions that emphasize acceptance of non-normative identities. The findings demonstrate that cinematography in Disney films operates as an active visual communication tool, shaping meaning and promoting new ideological frameworks within the realm of global popular culture.